Development of a Quran-Integrated Science Module to Empower the Religious Attitudes of Seventh-Grade Students in Ecology Material - Akbar, Irfan; Saputro, Sulistyo; Masykuri, Mohammad (Journal of Natural Science and Integration, 2025)
This study aims to develop a Quran-integrated science module to empower the religious attitudes of seventh-grade students in ecology material. The research employed a Design-Based Research (DBR) approach using Reeves' model, which consists of four stages: problem identification, design, iteration, and reflection. A total of 85 seventh-grade students from SMP Al Azhar Syifa Budi Solo and SMPIT Insan Mulia Surakarta were selected through random sampling and divided into control and experimental groups. Data analysis techniques included descriptive analysis for module feasibility based on expert validation, N-Gain score analysis to measure learning improvement, and an independent sample t-test to evaluate module effectiveness. The expert validation results showed a score of 88.8%, indicating the module’s high validity. Teacher and student responses toward the module were very positive, with scores of 90.35% and 94.29%, respectively. The independent sample t-test results revealed a significant difference (p < 0.05) in students' religious attitudes between the experimental and control groups, where students using the module showed higher religious attitudes. Additionally, the N-Gain analysis indicated a moderate improvement, with values of 0.37 for the experimental class and 0.32 for the control class. Based on these findings, it can be concluded that the developed Quran-integrated science module is both feasible and effective in empowering students' religious attitudes.Keywords: integrated Quran, religious attitude, science module